Consumption of energy-dense, nutrient-poor foods and hypertension in obese children - Mohammad Sulchan (Indonesian Pediatric Society Publishing House, 2014)
Background Obesity has become an increasingly important medical problem in children. Obesity-induced hypertension in childhood should be considered as a chronic medical condition that is likely to require long-term management of dietary patterns, especially for energy-dense, nutrient-poor (EDNP) food consumption. Objective To examine the contribution ofEDNP foods to daily energy and macronutrient intakes and to examine the relationship between intake of EDN P foods and the prevalence of hypertension in children. Methods Four hundred and forty children were randomly selected to participate. Weight and height were measured with precision electronic scales and fixed microtoise, respectively. Blood pressure (BP) measurements were performed by standard procedure. A 24-hour dietary recall was obtained by a trained interviewer to determine the intake of EDNP foods, which were clas sified to 4 major groups: visible fat, sweeteners, desserts, or salty snacks. The difference in mean was evaluated using paired Ttest. Logistic models were fitted to assess for an association between hypertension and the various characteristics. Results The proportion of children who were overweight (including obese) was 23 .2%. The prevalence of elevated BP was 10.5%, similar in boys and girls, with most of them having isolated elevated sys to lie BP. There was a relationship between BP and body mass index (BMI) in all children. Approximately 27% of total daily energy intake was contributed by all EDNP foods. Of the EDNP food subgroups examined, dessert and sweeteners contributed nearly 20% of total daily energy intake. In the highest one-third of subjects who consumed EDNP food, these foods provided 49% of total daily carbohydrate intake and 34% of total daily fat intake. Conclusion Eating patterns ofEDNP foods provide 49% of total daily carbohydrate intake and 34% of total daily fat intake. This EDNP food is independently associated with hypertension in children.